Arabidopsis CPK5 Phosphorylates the Chitin Receptor LYK5 to Regulate Plant Innate Immunity - Huang, Congcong; Yan, Yijia; Zhao, Huilin; Ye, Ying; Cao, Yangrong (Frontiers in Plant Science, 2020)
Chitin, a major component of the fungal cell wall, triggers plant innate immunity in Arabidopsis via a receptor complex including two major lysine motif receptor-like kinases, AtLYK5 and AtCERK1. Although AtLYK5 has been proposed to be a major chitin-binding receptor, the pseudokinase domain of AtLYK5 is required to mediate chitin-triggered immune responses in plants. In this study, 48 AtLYK5-interacting proteins were identified using immunoprecipitation and mass spectrometry assay. Among them, Arabidopsis CALCIUM-DEPENDENT PROTEIN KINASE 5 (AtCPK5) is a protein kinase interacting with both AtLYK5 and AtCERK1. Chitin-induced immune responses are inhibited in both Arabidopsis atcpk5 and atcpk5/6 mutant plants. AtLYK5 and AtLYK4 but not AtCERK1 are phosphorylated by AtCPK5 and AtCPK6 in vitro. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis and an in vitro kinase assay identified that Ser-323 and Ser-542 of AtLYK5 are important phosphorylation residues by AtCPK5. Transgenic Arabidopsis expressing either AtLYK5-S323A or AtLYK5-S542A in the atlyk5-2 mutant only partially rescue the defects in chitin-triggered MPK3/MPK6 phosphorylation. Overexpression of AtCPK5 could increase AtCERK1 protein level after chitin treatment. These data proposed a model in which AtCPK5 directly phosphorylates AtLYK5 and regulates chitin-induced defense responses in Arabidopsis.